Anti-Helicobacter pylori and urease inhibitory activities of resveratrol and red wine - Paulo, Luísa (2012)
There is considerable interest in alternative approaches for the eradication of Helicobacter pylori using biologically active compounds including antioxidants from a wide range of natural sources. In this work we have investigated the antibacterial properties of resveratrol towards different H. pylori strains. In addition we studied the inhibition of H. pylori urease by resveratrol and red wine. In those assays, resveratrol inhibited the growth of all the 17 H. pylori strains tested, with inhibition diameters ranging from 16 to 28 mm and minimum inhibitory concentration values varying from 25 to 100 mu g/mL, confirming its antimicrobial properties. Moreover, resveratrol and red wines showed an inhibitory effect on H. pylori urease activity, which is considered a virulence factor of this organism and essential for colonization and establishment of the infection. Further kinetic analysis revealed that inhibition occurred in a non-competitive and concentration-dependent manner. Overall, the results suggest that resveratrol and red wine may have potential for new therapy schemes that include natural products as an alternative therapeutic approach.